2002
DOI: 10.1016/s0886-3350(01)01352-9
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial decompensation after laser in situ keratomileusis

Abstract: We report the results of laser in situ keratomileusis (LASIK) in a 58-year-old woman with a history of corneal guttata in the right eye and mild Fuchs' dystrophy in the left eye. Preoperative pachymetry was 586 microm and 656 microm, respectively. The surgical treatment was +1.50 diopters (D) in the right eye and +3.25 D in the left eye. Surgery was performed using a VISX S2 Star laser and a Hansatome microkeratome with a 9.5 mm ring. Postoperatively, edema in the right eye resolved and pachymetry returned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 19 publications
0
29
0
1
Order By: Relevance
“…Cuando se ha realizado la técnica LASIK para corregir la hipermetropía en córneas con distrofia de Fuchs (5), la evolución ha sido hacia la descompensación corneal y queratoplastia. En el LASIK hipermetrópico, la ablación es periférica por lo que debe tenerse en cuenta la celularidad endotelial a este nivel (5). En los dos casos descritos de LASIK para corregir miopía en córneas con DPP (3), la pér-dida endotelial al año ha sido del 2,3%.…”
Section: Discussionunclassified
“…Cuando se ha realizado la técnica LASIK para corregir la hipermetropía en córneas con distrofia de Fuchs (5), la evolución ha sido hacia la descompensación corneal y queratoplastia. En el LASIK hipermetrópico, la ablación es periférica por lo que debe tenerse en cuenta la celularidad endotelial a este nivel (5). En los dos casos descritos de LASIK para corregir miopía en córneas con DPP (3), la pér-dida endotelial al año ha sido del 2,3%.…”
Section: Discussionunclassified
“…Specifically, these reports observed corneal decompensation after LASIK in patients with preoperative corneal guttata with and without associated corneal edema, highlighting the importance of avoiding LASIK in patients with signs of endothelial dysfunction. 14,15 Given these data, it is imperative, especially in patients with relatively thick corneas, that signs of corneal endothelial dysfunction including guttata and corneal edema be actively sought and excluded before LASIK is performed. In the absence of such clinical findings, we have found that outcomes after LASIK in patients with relatively thick corneas are comparable to outcomes in patients with more routine corneal thicknesses.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, the lack of this capacity may lead to accelerated endothelial cell loss and a compromised barrier. 27,28 Both Vroman et al 11 and Dastjerdi and Sugar 12 have reported cases of endothelial cell loss after LASIK in patients with Fuchs' dystrophy. While these studies support our observations, it is difficult to separate the effect of the refractive surgery on endothelial cells from the natural course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have documented the safety of myopic LASIK in patients with a healthy endothelium, 6-10 experience with LASIK in corneas with abnormal endothelium is limited. 11,12 In this study, the outcomes of LASIK in 4 patients (7 eyes) who had preoperative trace to 1C guttata and a family history of Fuchs' dystrophy were reviewed.…”
mentioning
confidence: 99%